LINE LASER LEVEL SEBAGAI ALAT BANTU PENENTUAN ARAH KIBLAT BERBASIS SELISIH AZIMUTH - Umi Kalsum; Rizka Aulia Kusumaningrum (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2026)
Determining the direction of the Qibla is a fundamental requirement in the construction and arrangement of Muslim places of worship. Various methods have been developed, but not all are readily accessible to the public due to technical and cost limitations. This article aims to conceptually examine the possibility of using a line laser level as a tool to help determine the direction of the Qibla based on the azimuth difference. The study was conducted through an analysis of the working principles of the line laser level and its suitability with the concept of azimuth difference in astronomy. Technically, a line laser level has the ability to project straight horizontal and vertical lines stably, thus functioning as a precise directional visualization on a flat surface. In the context of determining the direction of the Qibla, this characteristic is similar in function to the traditional istiwa'ain tool that uses a string as a straight guide, but with a more consistent level of stability and a lower potential for human error. Furthermore, compared to the relatively high cost of using a theodolite and requiring specialized technical skills, a line laser level can be seen as a more affordable and practical alternative for Qibla direction calibration needs at the community level. Thus, conceptually, the line laser level has the potential to be an applicable and alternative tool in determining the direction of the Qibla, as long as its use is based on correct azimuth calculations.